2020
DOI: 10.1113/ep088015
|View full text |Cite
|
Sign up to set email alerts
|

Circulating miRNAs are associated with sleep duration in children/adolescents: Results of the I.Family Study

Abstract: It is commonly recognized that sleep is essential for children's health, and that insufficient sleep duration is associated with negative health outcomes. In humans, sleep duration and quality are influenced by genetic, environmental and social factors. Epigenetic mechanisms, likewise, regulate circadian rhythms and sleep patterns. In the present study, we aimed to identify circulating microRNAs associated with sleep duration in a subsample of normal-weight European children/adolescents (n = 111) participating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…In relation to sleep quality, more adolescents from Seville and Tartu (51%) reported poor perceived sleep quality (PSQI ≥ 5) than did those from Reykjavik (41%). Our data agrees with similar studies in the participating cities [64,[74][75][76][77], as well as those reported in a longitudinal study that examined trends in the difficulty of sleeping in adolescents over 12 years [78].…”
Section: Sleep Qualitysupporting
confidence: 93%
“…In relation to sleep quality, more adolescents from Seville and Tartu (51%) reported poor perceived sleep quality (PSQI ≥ 5) than did those from Reykjavik (41%). Our data agrees with similar studies in the participating cities [64,[74][75][76][77], as well as those reported in a longitudinal study that examined trends in the difficulty of sleeping in adolescents over 12 years [78].…”
Section: Sleep Qualitysupporting
confidence: 93%
“…In the present, the analysis was conducted in a subsample of 58 OW/Ob children/adolescents of the I.Family Study (Belgium n=4, Cyprus n=4, Estonia n=10, Germany n=11, Hungary n=7, Italy n=9, Spain n=4, and Sweden n=9), with a complete dataset for the variables of interest. Information about educational level of parents and pubertal status were collected using a questionnaire filled in at home by parents [ 63 ].…”
Section: Methodsmentioning
confidence: 99%
“…In the current investigation, we aimed to confirm the association of hsa-miR-191-3p (MIMAT0001618) and hsa-miR-375 (MIMAT0000728) with early changes in insulin sensitivity in a new sample of children/adolescents through validation by SYBR green-based real-time quantitative RT-PCR (RT-qPCR). Experimental methods for miRNA extraction and screening from plasma samples have been earlier established [ 28 , 63 ]. Briefly, individual plasma samples were screened for haemoglobin levels, haemolysed samples were excluded from the analysis [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…Approval by the national ethics committees was obtained by each of the participating centers. Anthropometric characteristics, pubertal status, and dietary intake data were collected using standardized procedures; a full description of these methods has been previously published [31,32]. In each country, we first selected 20 children (n = 160) who retained overweight or obesity, i.e., who had a BMI z-score of more than + 1 at baseline and after 2 years at follow-up, respectively, and did not change more than ± 0.1 in BMI z-score per year (defined as overweight/obese) [33].…”
Section: Participantsmentioning
confidence: 99%
“…In the current investigation, we aimed to confirm the association of the candidate miRNAs with levels of CRP and the selected inflammatory biomarkers through validation by SYBR green-based real-time quantitative RT-PCR (RT-qPCR) in the new sample of children and adolescents with OW/Ob. Protocols for miRNA extraction and screening from plasma samples have been earlier published [30,32]. Individual plasma samples were first tested for hemoglobin levels and hemolyzed samples were excluded from the analysis [30].…”
Section: Mirna Profilingmentioning
confidence: 99%